Quality in governmental data retrieval: a study of public policy data on the internet - Moreira, Fabio Mosso [UNESP]; Santos Bisi, Pedro Henrique [UNESP]; Botega, Leonardo Castro [UNESP]; Santarem Segundo, Jose Eduardo [UNESP]; Goncalves Sant'Ana, Ricardo Cesar [UNESP] (Univ Federal Minas Gerais, Escola Biblioteconomia, 2020)
The use of the Internet to access government data is growing and presents possibilities for citizens to monitor the implementation of public policies. In the context of public policies for the agriculture sector, it is highlighted that these constitute a major factor in social and economic development, especially for small producers, who, in turn, need this informational content to participate and monitor actions. The government, through the Access to Information Law, is responsible for ensuring the wide dissemination of government programs, however, what is often observed is that the data are not made available as they should, mainly having problems related to the quality of the databases and recovery services. Thus, the objective of the research is to identify dimensions of quality involved in accessing government data on the Internet and apply them to the study of the data recovery process of the ProgramaNacional da Agricultura Familiar available on the Banco Central portal. Methodologically, a theoretical review was carried out to identify in the literature articles dealing with the issue of data quality in the government context, and, subsequently, a Content Analysis to identify categories that could represent such dimensions in a specific way for this domain. These dimensions were applied in the study of the data recovery process of a public agricultural policy aimed at the socio-economic development of small producers, and the results obtained to establish a perspective on how the issue of data quality can be observed in the studied scenario, as well as its implications. implications for access and ownership of content.
Keywords: Data retrieval; data quality; governmental data; public policy; PRONAF